Breast cancer causes and treatment: where are we going wrong? - Seymour CB (Dove Medical Press, 2013)
Colin B Seymour, Carmel MothersillMedical Physics and Applied Radiation Sciences Department, McMaster University, Hamilton, ON, CanadaAbstract: This discussion paper seeks to provoke thoughts about cancer research in general, and why breast cancer in particular is not yet “curable”. It asks the question – are we looking at the disease in the right way? Should we regard cancer as a progressive state, which is part of aging? Should we tailor treatment to “reset” the system or slow progression rather than try using toxic and aggressive therapy to kill every cancer cell (and sometimes also the patient)? The thesis is presented that we need to revisit our fundamental beliefs about the disease and then ask why we cling to beliefs that clearly are no longer valid. The paper also questions the role of ethics boards in hampering research and discusses the concept that breast cancer is an industry with vested interests involving profiteering by preventive, diagnostic, and therapeutic players. Finally, the paper suggests some ways forward based on emerging concepts in system biology and epigenetics.Keywords: breast cancer, causes, treatment, questioning paradigms